Industrialização e o desenvolvimento econômico do município de Estância (SE) : 2002 a 2012 - Santos, Heloisia Fontes (2015)
The paper analyzes the industrialization in the Estância municipality by reference to the 90 years to 2000. In this interregnum, it was found that the effects of economic opening turned some productive sectors in the Brazilian economy, especially the textile sector in the resort municipality. According to IBGE (2012) at the end of the 90 municipal PIB accounted for 7.35% of the State's participation, but in 2012 this percentage dropped to 4.7%. Although the Estancia’s Industry PIB in VAB in 2002 accounted for 10.0% of the state share, in 2012 this percentage dropped to 6.8% of Sergipe industry. Also it is noticed in the 2000s the number of Estancia’s industry establishments has grown in some activities, influenced by the new cycle of expansion of the Brazilian economy and the support of the Industrial Development Sergipe Program - PSDI, resuming growth with the arrival of new companies since 2009. Thus, to study the effects of Estancia’s municipal, industrial PIB, total and industrial establishments, the total industrial employment, we used the structuralist method with comparative analysis and explanatory research sectors, of this municipality from 2002 to 2012.